Rapid adhesive platelet count in whole blood - Eastham, Robert D. (1964)
A proportion of the platelets in whole blood become more adhesive when treated with adenosine diphosphate. After these platelets have adhered to the walls of a polystyrene container, E.D.T.A. is added and a count is made of the remaining platelets in the blood sample. By subtracting this latter count from the total whole blood platelet count a whole blood adhesive platelet count is obtained. For rapidity and accuracy, an electronic cell counter is used for each platelet count.